2010
DOI: 10.1071/sh09072
|View full text |Cite
|
Sign up to set email alerts
|

Do women use dental dams? Safer sex practices of lesbians and other women who have sex with women

Abstract: Abstract. Dental dams are distributed and promoted in some safer sex campaigns for use in oral sex. However, whether and how often dams are used for sex between Australian women remains unknown. We investigated the use of dental dams for sex by lesbians and other women who have sex with women, and the relationship between dam use and sexual risk for this group. In 2004, a self-completion questionnaire was distributed to women attending the Sydney Gay and Lesbian Mardi Gras Fair Day and lesbian community venues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 6 publications
3
25
1
1
Order By: Relevance
“…Interestingly, there were no definable characteristics associated with avoidance of barrier use in the present study. Sexual risk taking among WSW has been reported [17]; the present data both confirm this finding and provide an important addition by assessing differential use of barriers with certain sexual activities and in certain sexual contexts.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Interestingly, there were no definable characteristics associated with avoidance of barrier use in the present study. Sexual risk taking among WSW has been reported [17]; the present data both confirm this finding and provide an important addition by assessing differential use of barriers with certain sexual activities and in certain sexual contexts.…”
Section: Discussionsupporting
confidence: 84%
“…There have been many studies assessing the risk of STIs among WSW, including assessment of barrier protection methods [14–19]. However, most of these studies involved focus groups [14,15] and/or surveys assessing the use of a specific barrier method, or STIs with no consideration of barrier use [16–19]. We are unaware of any large‐scale surveys involving a large number of WSW and including details of different barrier protection for specific sexual activities.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings furthermore suggest the need for research that addresses WSW’s awareness of HIV and STI risk and their engagement in sexual risk practices; few studies [12], [50] have done so thus far, while some studies have shown that adoption of safer sex practices among WSW is rare (e.g., [51]). In addition, we need to understand how accurate, appropriate and complete counseling could be provided to WSW living with HIV in order to prevent transmission to other female sex partners.…”
Section: Discussionmentioning
confidence: 90%
“…While relying on trust to determine the extent to which safer sex is practiced is not specific to sexual minority women, women in this study reported that their women partners were seen as safer partners because they trusted them to take care their own health, protect them from risk, and to disclose histories of prior or current infections [45]. Previous studies of sexual minority women have also noted that women generally trust their women partners and as such do not perceive the need to practice safer sex [40, 46, 47]. Together, these studies suggest the need for sexual minority relevant health education that focuses specifically on safer sex practices with women partners, including partner communication.…”
Section: Discussionmentioning
confidence: 99%